2009
DOI: 10.1016/j.juro.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback Training for Lower Urinary Tract Symptoms: Factors Affecting Efficacy

Abstract: Biofeedback therapy can be effective in children with dysfunctional voiding and urinary tract infection. Children with a staccato voiding pattern may require a minimum of 3 visits to improve the voiding pattern. Children who complete 3 sessions are more likely to succeed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
1
15
1
1
Order By: Relevance
“…While our study suggests that BFB works to lower the symptom score and thus is effective, it does not address the issue of cost which can be substantial for both in our series and others [9] the number of BFB office visits ranged anywhere from 1 to 9. The next generation of BFB devices should become more portable to allow for BFB at home [15] in a more natural setting.…”
Section: Figurementioning
confidence: 62%
See 2 more Smart Citations
“…While our study suggests that BFB works to lower the symptom score and thus is effective, it does not address the issue of cost which can be substantial for both in our series and others [9] the number of BFB office visits ranged anywhere from 1 to 9. The next generation of BFB devices should become more portable to allow for BFB at home [15] in a more natural setting.…”
Section: Figurementioning
confidence: 62%
“…Protocols for BFB, which types of patients should be referred, which outcome measures should be used and how long patients should be treated, are variable among practitioners [3,9,10]. Positive clinical outcomes of BFB have included reduction in post-void residual urine, improved vesicoureteral reflux, increased bladder capacity, reduction of EMG activity during voiding, and a reduced incidence of UTIs [9,11].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…showed that some parameters are able to predict the success of BFM therapy (Drzewiecki et al, 2009). The Authors noted that compliance and commitment during the treatment are both determinant factors, considering that at least 6 sessions are required for pediatric patients and that the probability of flow normalization after the third session are reduced to 5%.…”
Section: Non-neurologic Causesmentioning
confidence: 99%
“…However, EMG was not used to define the presence of dysfunctional voiding. Drzewiecki et al [18] reviewed possible factors for success in 77 children who underwent either animated or nonanimated biofeedback. Daytime and nighttime wetting was present in 61% of patients prior to treatment.…”
Section: Biofeedback Efficacymentioning
confidence: 99%